The Strategic Role of Teacher Communication in Shaping a Learning Environment that Promotes Student Learning Motivation: A Qualitative Study - Fadillah, Zikry Indra; Hashim, Roslan; Aini, Sharifah (Journal Sains and Education, 2025)
This research delves into the pivotal role of teacher educational communication in shaping the learning environment and influencing student learning motivation. Through a descriptive research approach employing qualitative methods, observations, interviews, and documentation were utilized for data collection. The results indicate that teachers significantly influence student learning motivation through their presence, guidance, and encouragement, fostering conducive learning atmospheres. Effective communication strategies tailored to individual student needs, incorporating interactive techniques, and integrating technology were found to enhance student engagement and interest in learning. Moreover, collaborative efforts between teachers, parents, and the broader community contribute to a supportive learning environment, nurturing students' academic and personal growth. The study underscores the importance of teacher educational communication in shaping the learning environment, fostering positive relationships, and motivating students to achieve their full potential, thereby empowering them to succeed academically and thrive personally.